Study of gasification reaction of cokes excavated from pilot blast furnace - Hilding, T.; Sahajwalla, V.; Gupta, S.; Björkman, Bo; Sakurovs, R.; Grigore, M. (Luleå tekniska universitet, Industriell miljö- och processteknik, 2004)
Fundamental understanding of coke reactions with gas, metal and slag phases is essential for ensuring smooth operation and optimisation of coke performance in existing and advanced blast furnace process, and is dictated by coke properties and blast furnace process conditions. In this study, coke samples excavated from LKAB's Experimental Blast Furnace (EBF) at MEFOS in Luleå, Sweden were collected. The centreline quenched coke samples from different zones of this EBF were used to observe the influence of in-furnace reactions on the evolution of coke properties and their associations with CO2 reactivity. Carbon structure of coke was found to increasingly ordered, silicon and iron concentration in the coke samples decreased, while alkali concentration particularly potassium and sodium were found to increase as the coke descended towards lower part of the EBF. Both isothermal and non-isothermal reactivity based on TGA measurements showed that coke reactivity towards CO2 is increased as coke descends towards cohesive zone despite increasing order of carbon structures. Increased reactivity of cokes at lower parts of EBF was related to alkali enrichments of cokes. The study further shows that increased alkali components in cokes have a strong impact on CO2 gasification in EBF such that influence of coke graphitisation could be compensated by catalytic influence of alkalis. To further assist with development of understanding of reactivity of coke, gasification studies were also conducted in a fixed bed reactor at 900ºC using a series of cokes made from Australian coals (varying in rank, maceral and mineral matter). The CO2 reactivity of cokes in a fixed bed reactor was also found to be strongly influenced by the coke minerals compared to carbon structure. Further studies are required to provide a critical insight into the influence of key parameters such as coke graphitisation and mineral reactions on coke gasification particularly at higher temperatures. Godkänd; 2004; 20061210 (ysko)